Návrh modelu služeb sítě pro firmu Techniserv IT s.r.o. - Lavický, Jindřich (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Bakalářská práce popisuje návrh modelu služeb sítě pro firmu Techniserv IT s.r.o. Analyzuje současný stav IT infrastruktury v organizaci a navrhuje vhodné systémové a ekonomické řešení. Popisuje jednotlivé oblasti služeb sítě a jejich výhody. Detailně se zaměřuje na oblast nasazení služeb sítě, která je pro tuto práci klíčová. Na závěr navrhuje řešení a vyhodnocuje jejich přínos podniku.

The bachelor thesis describes a proposal of network services model for Techniserv IT s.r.o. company. It analyses the present state of IT infrastructure in organization and suggests appropriate and economical solutions. It describes constituent areas of network services and their advantages. In detail, it focuses on the area of network services implementation, which is crucial for this type of work. At the end, it proposes solutions and evaluates their assets for a company.
lmprovement Proposal of Network Services Model for Techniserv IT s.r.o. company
Keywords: Služby sítě; DNS; DHCP; NTP; Microsoft; Windows Server 2008; Network services; DNS; DHPC; NTP; Microsoft; Windows Server 2008